ASSESSING THE ECONOMIC CONSEQUENCES OF FUEL SUBSIDY REMOVAL ON ROAD TRANSPORTATION COST IN DELTA STATE, NIGERIA - Elvis, Adogbeji Oghenenyerhovwo; Bright, Ogbe (Universitas Islam Malang, 2025)
The removal of fuel subsidies in Nigeria remains a highly debated policy, with some experts viewing it as a driver of poverty and others as a fiscal reform opportunity to reallocate national resources. This study examines the economic consequences of fuel subsidy removal on road transportation costs in Delta State, focusing on its effects on commuters and transport operators while identifying viable policy interventions. Guided by the Resource Dependency Theory (RDT), the study employed a descriptive survey design. Data were collected through structured questionnaires administered to 240 purposively selected respondents, and analyzed using simple percentage and chi-square tests. The findings reveal that the removal of fuel subsidies significantly increased transportation costs in Delta State, while existing government measures to cushion the effects have shown limited success. The study recommends that the Delta State Government should revitalize the Delta Mass Transit system (popularly known as Uduaghan Bus) and promote the adoption of electric vehicles through targeted subsidies to mitigate rising transportation costs.